2018
DOI: 10.1080/10615806.2018.1498277
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and behavioral reaction of low and high sensation seekers differ in responding to a sport-specific stressor

Abstract: Individuals seem to react physiologically differently to a sport-specific stressor, depending on their level of sensation seeking. HSS seem to be less strained, and seem to perform better. These findings might be relevant not only for the evaluation of (sport-) psychological interventions but also for other contexts (e.g., special forces).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
2
20
2
1
Order By: Relevance
“…As a coping-related personality trait, sensation seeking did not predict shooting performance nor stress responses in the LS and HS scenario. This finding does not support hypothesis 4 and contradicts a body of research suggesting stress-buffering effects of sensation seeking (Couture et al, 2008; Tschiesner, 2012; Frenkel et al, 2018; Frenkel et al, unpublished). Therefore, further investigations into the role of sensation seeking are necessary to allow deeper conclusions.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…As a coping-related personality trait, sensation seeking did not predict shooting performance nor stress responses in the LS and HS scenario. This finding does not support hypothesis 4 and contradicts a body of research suggesting stress-buffering effects of sensation seeking (Couture et al, 2008; Tschiesner, 2012; Frenkel et al, 2018; Frenkel et al, unpublished). Therefore, further investigations into the role of sensation seeking are necessary to allow deeper conclusions.…”
Section: Discussioncontrasting
confidence: 90%
“…Possibly, variation in performance under stress can be explained by individual differences in task-relevant personality traits that become activated depending on the presence of trait-relevant situational cues (Tett and Gutermann, 2000). In case of extreme stress situations, literature has shown that self-control (Englert and Bertrams, 2015; Landman et al, 2016) and sensation seeking (Zuckerman, 1994; Frenkel et al, 2018; Frenkel et al, unpublished) affect psychophysiological stress responses and performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1978, Williams et al suggested that rock climbing bring forth an anxiety type of psychological stress than a physical one. Nowadays, this psychophysiology perspective can be analyzed by established indicators of emotional state supported by physiological stress parameters or by personality characteristics . In the last years, the literature relates rock climbing to physiological, anthropometric, and sports‐related injuries and suggests that psychological variables, such as problem‐solving, memory recall, and anxiety, may be crucial to the success of climbing .…”
Section: Introductionmentioning
confidence: 99%